The impact of education on the subjective discount rate in Ugandan villages - Michal Bauer; Julie Chytilová (Institute for the Study of Labor (IZA), 2009)
Heterogeneity in time discounting may reinforce the existing barriers to save and invest faced by rural populations in developing countries. We elicit a subjective discount rate for a varied sample of Ugandan villagers. In accordance with other studies, we have found the discount rate to decrease with education. We examine this correlation further by testing the causal effect of education and exploit two different sources of its variation: school frequency across villages and the number of the respondents' school-going years that overlap with the era of the dictator Idi Amin's rule. For men, we find that education has a significant impact on their discount rate, similar in magnitude for both types of instruments and robust to observable characteristics. This finding highlights the importance of education in development.
urn:nbn:de:101:1-20090327242
Keywords: C93; D91; O12; 330; Time discounting; patience; education; economic development; Uganda; Sparen; Investition; Landbevölkerung; Zeitpräferenz; Soziale Diskontrate; Bildungsniveau; Ländliche Entwicklung; Uganda